Coating composition for cooking utensils, baking utensils and other cooking utensils comprising acrylic polymer

By using a coating composition composed of acrylic emulsions and crosslinked polymers, the problems of viscous degradation and chemical erosion of existing heat-resistant coatings at high temperatures are solved, the dual properties of flexibility and heat resistance are achieved, and the dependence on perfluoro and polyfluoroalkyl substances is reduced.

CN119894999APending Publication Date: 2025-04-25PPG INDUSTRIES OHIO INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380059741.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-15
Filing Date
2023-08-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing heat-resistant coatings have problems with viscous degradation and chemical erosion when used at high temperatures and are subject to regulatory scrutiny for perfluoro and polyfluoroalkyl substances, and new coating compositions are needed to replace traditional fluoro and silicon-based polymers.

Method used

A coating composition consisting of an acrylic emulsion, a filler material and water is employed, which comprises a first polymer formed from the polymerization of ethylenically unsaturated monomers containing acid monomers and a second polymer formed from the polymerization of the linking monomers, with crosslinked covalent bonds and non-covalent interactions between the two.

Benefits of technology

The coating composition is able to maintain flexibility and heat resistance at high temperatures, provide a non-stick mold release surface, and reduces dependence on perfluoro and polyfluoroalkyl substances, meeting the dual requirements for environmental protection and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894999A_ABST
    Figure CN119894999A_ABST
Patent Text Reader

Abstract

A coating composition that can form a flexible heat resistant coating on a substrate such as a cookware, baking appliance or other cooking appliance is derived from and / or comprises an acid-rich acrylic polymer. The coating composition may be water-based or solvent-based, and may be produced or formulated via a variety of routes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a coating composition comprising an acrylic polymer for use in cookware, bakeware or other cooking utensils, wherein the coating formed from the composition exhibits flexibility and heat resistance. The coating composition can be applied to the interior or food contact surface and / or non-food contact surface of the cookware, bakeware or other cooking utensils. Background Art

[0002] Heat resistant coatings are often applied to substrates such as cookware, bakeware, cooking utensils such as grills, and other substrates to provide functionality such as aiding heat transfer, providing a non-stick release surface, and / or providing a decorative color or aesthetic finish.

[0003] Currently, the cookware and bakeware industry relies on both fluorine-based and silicon-based polymer coating technologies to provide non-stick and easy-to-clean properties to metal surfaces as well as to withstand high temperature cooking, such as up to 260°C. The strength of the covalent carbon-fluorine (CF) bond makes the polymer resistant to both chemical attack and thermal degradation. When considering the complete life cycle of the material, the strength of the CF bond, while beneficial for many applications including non-stick cookware coatings, has come under increasing regulatory scrutiny related to per- and polyfluoroalkyl substances (PFAS).

[0004] What is needed are coating compositions that are improvements over the above. Summary of the invention

[0005] The present disclosure provides a coating composition, which includes an acrylic emulsion, a filler material and water, the acrylic emulsion including particles formed by a first polymer and a second polymer, the filler material being present in an amount of at least 2 wt.% based on the total weight of the coating composition. The first polymer is polymerized from ethylenically unsaturated monomers including acid-containing monomers. The second polymer is chemically different from the first polymer. The second polymer is polymerized from ethylenically unsaturated monomers including linking monomers. The first polymer and the second polymer have at least one of a cross-linking covalent bond and a non-covalent interaction between the acid-containing monomer of the first polymer and the linking monomer of the second polymer.

[0006] The present disclosure further provides a method for coating a substrate with a coating composition, the method comprising applying the coating composition to the surface of the substrate, the coating composition comprising an acrylic emulsion, a filler material and water, the acrylic emulsion comprising particles formed of a first polymer and a second polymer, the filler material being present in an amount of at least 2 wt.% based on the total weight of the coating composition; and curing the coating composition to form a coating. In addition, the present disclosure provides an article coated according to the above method, the article being selected from cookware articles, bakeware articles and cooking utensils.

[0007] The present disclosure also provides an acrylic emulsion composition, which includes an aqueous medium; a neutralizer; and emulsion particles. The emulsion particles include a film-forming resin containing a siloxane polymer; and an acrylic polymer polymerized from ethylenically unsaturated monomers including an acid-containing monomer. The film-forming resin is emulsified in the aqueous medium by the acrylic polymer.

[0008] The present disclosure further provides a method for coating a substrate with a coating composition, the method comprising applying the coating composition to the surface of the substrate, the coating composition comprising an acrylic emulsion composition, the acrylic emulsion composition comprising an aqueous medium; a neutralizer; and emulsion particles; and curing the coating composition to form a coating. In addition, the present disclosure provides an article coated according to the above method, the article being selected from cookware products, bakeware products, and cooking utensils.

[0009] The present disclosure also provides a coating composition, which comprises a solvent medium; a film-forming resin, the film-forming resin comprising a siloxane polymer; and an acrylic polymer polymerized from ethylenically unsaturated monomers including acid-containing monomers. The ethylenically unsaturated monomers have a content of 20 wt.% to 70 wt.% of the acid-containing monomers based on the total weight of the ethylenically unsaturated monomers.

[0010] The present disclosure further provides a method for coating a substrate with a coating composition, the method comprising applying the coating composition to the surface of the substrate, the coating composition comprising a solvent medium; a film-forming resin, the film-forming resin comprising a siloxane polymer; and an acrylic polymer polymerized from ethylenically unsaturated monomers including acid-containing monomers; and curing the coating composition to form a coating. In addition, the present disclosure provides an article coated according to the above method, the article being selected from cookware articles, bakeware articles, and cooking utensils. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] By referring to the following description in conjunction with the accompanying drawings, the above and other features and advantages of the present disclosure and the manner in which they are obtained will become more apparent, and the present disclosure itself will be better understood.The above and other features of the present disclosure may be used in any combination or arrangement.

[0012] Figure 1 Flowcharts showing four exemplary pathways for producing coating compositions according to the present disclosure;

[0013] Figure 2A A substrate coated with a coating composition of the present disclosure is shown;

[0014] Figure 2B Shows Figure 2A a cross-section of a substrate; and

[0015] Figure 3Particle size reduction is shown to determine the wt. % of acrylic emulsifier on the film-forming resin required to achieve and stabilize the median volume distribution (D50) in the formation of the silicone acrylic emulsion.

[0016] Corresponding reference characters indicate corresponding parts throughout the several views.The examples set out herein illustrate the disclosure, and such examples should not be construed as limiting the scope of the disclosure in any way. DETAILED DESCRIPTION

[0017] The present disclosure provides coating compositions that can be applied to interior or food contact surfaces and / or exterior or heat contact surfaces of cookware or bakeware articles. In addition, the present disclosure provides coating compositions that can be formulated as aqueous or water-based compositions or as solvent-based compositions for application to cookware, bakeware or other cooking utensils to form a heat-resistant but flexible non-stick coating with good release properties.

[0018] I. Definitions

[0019] For the purpose of the following detailed description, it should be understood that the present disclosure may take various alternative changes and step sequences, unless explicitly indicated to the contrary. In addition, except in any operating examples, or where otherwise indicated, all numbers used in the specification and claims to represent, for example, the quantity of ingredients should be understood to be modified by the term "about" in all cases. For example, the numerical range provided for the weight percentage of a component or the amount of an added component should be interpreted as being modified by the term "about". Therefore, unless indicated to the contrary, the numerical parameters set forth in the following specification and the attached claims are approximate values ​​that can be changed according to the desired properties to be obtained by the present disclosure. At least, and not attempting to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be interpreted according to the number of reported significant figures and by applying the usual rounding techniques.

[0020]

[0013] While the numerical ranges and parameters setting forth the broad scope of the present disclosure are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements.

[0021] While specific examples of the present disclosure have been described above for purposes of illustration, it will be apparent to those skilled in the art that numerous changes may be made in the details of the disclosure without departing from the present disclosure as defined in the appended claims.

[0022] Furthermore, it should be understood that any numerical range described herein is intended to include all subranges subsumed therein. For example, a range of "1 to 10" is intended to include all subranges from the recited minimum value of 1 to the recited maximum value of 10 (and including the minimum and maximum values), i.e., having a minimum value equal to or greater than 1 and a maximum value equal to or less than 10.

[0023] Unless specifically stated otherwise, the use of the singular includes the plural and the plural encompasses the singular. Furthermore, unless specifically stated otherwise, the use of "or" means "and / or," even though "and / or" may be explicitly used in some instances.

[0024] The use of the term "non-stick" herein is intended to refer to a coating having anti-stick properties, particularly when the coating is applied to cookware and / or bakeware. When the coating is applied to cookware and / or bakeware, the non-stick may pertain to food anti-stick properties including food soil anti-stick properties.

[0025] "Core-shell polymer" is used herein based on the theory that, in forming the latex particles of the present disclosure, one stage of polymerization results in the formation of a polymerized surfactant that becomes located in the exterior or shell region of the final particle, and another stage of polymerization results in the formation of a core within the interior of the shell. Although there is evidence that such a "core-shell" morphology does exist, its presence is not essential to the function of the present disclosure.

[0026] "Shell" refers to the polymerized surfactant located in the exterior or shell region of the final particle formed during polymerization.

[0027] "Core" relates to the core formed within the shell during polymerization.

[0028] As used herein, a "wet" coating composition refers to a liquid or uncured coating composition that includes water and / or volatile components.

[0029] As used herein, a "dry" coating composition refers to a cured coating composition that is substantially free of water and / or volatile components.

[0030] As used herein, "substrate" and "article" refer to an object or other item having a surface to which a coating composition can be applied.

[0031] "Solids" refers to the nonvolatile components present in the combination of volatile and nonvolatile components. As used herein, weight percent on a "solids" basis refers to the amount of the component based on the total weight of the precondensed silicone resin.

[0032] "Resin solids" refers to the solid components that make up the binder or film-forming component of the composition. As used herein, weight percent based on "resin solids" refers to the amount of the component based on the total weight of the binder or film-forming component of the composition.

[0033] "Siloxane monomer" and "siloxane polymer" refer to monomers or polymers, respectively, that contain alternating silicon-oxygen bonds, such as O-Si-O and / or Si-O-Si bonds.

[0034] "Emulsion" refers to a fine dispersion of one liquid in another liquid. As used herein, "silicone resin coating emulsion" refers to an emulsion comprising a silicone resin coating composition dispersed in a solvent. As used herein, "emulsion solution" refers to a dilute emulsion comprising a silicone resin coating composition dispersed in a solvent.

[0035] "Aqueous" refers to a composition formulated with and consisting essentially of one or more aqueous solvents. As discussed herein, an aqueous composition can have a VOC level of less than 420 g / L.

[0036] "Solvent-borne" refers to a composition formulated with and consisting essentially of one or more non-aqueous solvents. As discussed herein, a solvent-borne composition can have a VOC level greater than 420 g / L.

[0037] II. Coating Composition

[0038] The coating compositions of the present disclosure can form flexible heat-resistant coatings and are derived from and / or include acrylic polymers. The acrylic polymers can be acid-rich, meaning that the polymers as discussed herein are formed from a relatively high percentage of acid-containing monomers based on the total weight of the polymer. The coating compositions can be solvent-based, or alternatively, aqueous or water-based, and the coating compositions can be produced or formulated via a variety of reaction pathways.

[0039] like Figure 1 As shown, four exemplary routes for forming a coating composition according to the present disclosure include a first route 10, a second route 20, and a third route 30 for formulating a water-based coating composition, and / or a fourth route 40 for formulating a solvent-based coating composition.

[0040] For example, each of the coating compositions can include an acid-rich acrylic polymer, which can be neutralized, as described further below, and / or can be blended with, for example, another polymer / resin, such as a silicone polymer / resin.

[0041] The acid-rich acrylic polymer can be formed by free radical polymerization, wherein ethylenically unsaturated monomers are polymerized. The acid-rich acrylic resin can be neutralized to form an acid-rich acrylic emulsifier or emulsifier, and can be used to emulsify a film-forming resin in an aqueous medium, and the emulsified film-forming resin can be formulated into a coating composition.

[0042] A. Acid-rich acrylic polymer

[0043] The acid-rich acrylic polymer can be formed from a first mixture of monomer components that undergo polymerization.The monomers can be ethylenically unsaturated monomers selected to produce a polymer with excess acid functionality such that the polymer particles are stable in an aqueous medium when neutralized with a base.

[0044] The first monomer mixture may include monomers of exemplary formulas (I), (II), and (III):

[0045]

[0046] wherein R is H or an alkyl group, and R1 is an alkyl, aryl or silyl group.

[0047] The monomer mixture can have a weight percentage of acid group-containing monomers of 10 wt.%, 15 wt.%, or 30 wt.% to 40 wt.%, 60 wt.%, or 90 wt.%, based on the total weight of the monomers, or in any range using any two of the foregoing as endpoints, such as 10 wt.% to 90 wt.%, 15 wt.% to 60 wt.%, or 30 wt.% to 40 wt.%.

[0048] The desired combination of coating application and performance at these high acid levels is achieved by using at least one acid group-containing monomer. Suitable acid group-containing monomers used in the first polymerization can be acrylic acid and methacrylic acid, which can be in a weight ratio of 1:10 to 10:1, 1:3 to 3:1, or 2:3 to 3:2 when used alone or in combination, or in any range using any two of the foregoing as endpoints. Other suitable acid monomers can include itaconic acid, maleic acid, fumaric acid, phosphating acrylate / methacrylate, and sulfonated acrylate / methacrylate.

[0049] The resulting acrylic polymer can have an acid number of 10 mg KOH, 50 mg KOH, 70 mg KOH, 90 mg KOH, 100 mg KOH, 120 mg KOH, or 125 mg KOH to 150 mg KOH, 200 mg KOH, 300 mg KOH, 400 mg KOH, 500 mg KOH, 600 mg KOH, or 700 mg KOH, or in any range using any two of the foregoing as endpoints, such as 10 mg KOH to 700 mg KOH, 50 mg KOH to 600 mg KOH, 70 mg KOH to 500 mg KOH, 90 mg KOH to 400 mg KOH, 100 mg KOH to 300 mg KOH, 120 mg KOH to 200 mg KOH, or 125 mg KOH to 150 mg KOH, wherein the acid number can be measured using a Metrohm 798 MPT Titrino automatic titrator manufactured by Metrohm AG according to ASTM D 1478. D4662-15(2020) confirmed.

[0050] In addition to the monomer containing an acid group, the first monomer mixture may also include an alkyl acrylate (such as methyl acrylate, ethyl acrylate, propyl acrylate or butyl acrylate) or a corresponding methacrylate, including a mixture thereof. In the first stage polymerization, a higher molecular weight acrylic monomer may also be used as a comonomer, such as 2-ethylhexyl acrylate, cyclohexyl acrylate, n-hexyl acrylate, lauryl acrylate, tridecyl acrylate, isobornyl acrylate, stearyl acrylate, n-decyl methacrylate, benzyl acrylate, isobutyl acrylate, dicyclopentyl acrylate, isodecyl acrylate, tert-butyl acrylate, palmityl acrylate, ethoxyethyl acrylate, methoxybutyl acrylate, 2-(2-ethoxyethoxy)ethyl acrylate, 2-phenoxyethyl acrylate, tetrahydrofurfuryl acrylate, methoxylated tripropylene glycol monoacrylate, 1H-, 1H-, 5H-octafluoropentyl acrylate, trimethylsiloxyethyl acrylate or the corresponding methacrylates described above.

[0051] The first monomer mixture can have a weight percentage of the optional acrylate monomer of 0 wt.%, 5 wt.%, 10 wt.%, 15 wt.%, or 20 wt.%, to 25 wt.%, 30 wt.%, 35 wt.%, or 40 wt.%, or within any range using any two of the foregoing as endpoints, such as 0 wt.% to 40 wt.%, 5 wt.% to 35 wt.%, 10 wt.% to 30 wt.%, or 20 wt.% to 25 wt.%, where the wt.% is based on the total weight of the first monomer mixture.

[0052] One or more non-acrylate monomers with α-β ethylenic unsaturation are optionally included in the first monomer mixture. These additional non-acrylate monomers can serve as diluents to reduce the cost of latex, or serve as modifiers to improve the properties of polymers. Non-acrylate monomers can include styrene, ethyl styrene, vinyl esters, 1,4-butadiene, acrylonitrile, vinyl ether, acrylamide, fumarate, etc.

[0053] The first monomer mixture can have a weight percentage of optional non-acrylate monomers of 0 wt.%, 5 wt.%, 10 wt.%, 15 wt.%, or 20 wt.%, to 25 wt.%, 30 wt.%, 35 wt.%, 40 wt.%, 45 wt.%, 50 wt.%, 55 wt.%, or 60 wt.%, or in any range using any two of the foregoing as endpoints, such as 0 wt.% to 60 wt.%, 5 wt.% to 55 wt.%, 10 wt.% to 50 wt.%, 15 wt.% to 45 wt.%, 20 wt.% to 40 wt.%, or 25 wt.% to 35 wt.%, where the wt.% is based on the total weight of the first monomer mixture.

[0054] The polymerization to form the acidic acrylic polymer can occur in the absence of a chain transfer agent. Chain transfer agents are compounds used to control chain length during synthesis to achieve certain mechanical and processing properties. Absence of a chain transfer agent means that the polymerization occurs in the presence of less than 0.1 wt.% of a chain transfer agent, where the weight percentage is defined by the total weight of the reactants of the polymerization reaction.

[0055] The resulting acid-rich acrylic acid polymer may be a polymer represented by exemplary formula (IV):

[0056]

[0057] wherein R is H or an alkyl group, and R1 is an alkyl, aryl or silyl group.

[0058] like Figure 1 As shown and discussed further below, the acidic acrylic polymer 11 can be used to form a water-borne coating composition or a solvent-borne coating composition.

[0059] The coating compositions provided by the present disclosure may include an acrylic polymer in an amount of 2 wt.%, 4 wt.%, or 8 wt.% to 12 wt.%, 15 wt.%, or 20 wt.%, or within any range using any two of the foregoing as endpoints, such as 2 wt.% to 20 wt.%, 4 wt.% to 15 wt.%, 8 wt.% to 10 wt.%, wherein the wt.% is based on the total weight ("wet" weight) of the coating composition.

[0060] The coating compositions provided by the present disclosure may include an acrylic polymer in an amount of 2 wt.%, 4 wt.%, or 6 wt.% to 8 wt.%, 12 wt.%, or 15 wt.%, or within any range using any two of the foregoing as endpoints, such as 2 wt.% to 15 wt.%, 4 wt.% to 12 wt.%, 6 wt.% to 8 wt.%, wherein the wt.% is based on the total weight of the solid components of the coating composition ("dry" weight).

[0061] i. Water-based coating composition

[0062] The waterborne coatings 100a, 100b can be formulated using a variety of different components. Figure 1 As shown, routes 10, 20, and 30 can all produce water-based coating compositions 100a, 100b.

[0063] a. First path 10

[0064] If via Figure 1 As exemplified by the pathway 10 of , an acidic acrylic polymer 11 can be neutralized to produce an aqueous acid-rich acrylic emulsifier 12, wherein the acrylic emulsifier 12 can alternatively be referred to as an acid-rich acrylic soap. The acrylic emulsifier 12 can be a core polymer formed by partially neutralizing the acid groups of the acrylic polymer 11 with an appropriate basic compound. Suitable basic compounds can include organic bases and inorganic bases. Bases that can be used for neutralization include alkali metal hydroxides, ammonia, ammonium hydroxide, methylethanolamine, and diethanolamine. For a particular composition, a person skilled in the art can easily determine the minimum degree to which the acid groups must be neutralized in order to provide stability to the latex. Suitable neutralizing agents can include amines such as dimethylethanolamine, ammonia, triethanolamine, dimethylethylethanolamine, or N', N'-dimethylaminopropylamine or alkali metal salts such as sodium hydroxide or potassium hydroxide.

[0065] The resulting acidic acrylic emulsifier 12 can be represented by exemplary formula (V):

[0066]

[0067] wherein R is H or an alkyl group, and R1 is an alkyl, aryl or silyl group.

[0068] The acidic acrylic emulsifier 12 can then undergo polymerization with a second monomer mixture to produce a film-forming resin. The film-forming resin can be a hybrid core-shell acrylic 14.

[0069] The monomer components of the second monomer mixture for polymerizing the acrylic emulsifier to form the latex particle core can be selected from a variety of ethylenically unsaturated monomers, including optional acrylates and non-acrylate unsaturated monomers or combinations of the two discussed above in conjunction with the first monomer mixture. Small acrylates, i.e., those with less than three carbon atoms in the side chain, can be used. Acrylates with four or more carbon atoms in the side chain, such as butyl acrylate, can be included in small amounts, such as less than 10% by weight of the second monomer mixture. Non-acrylate unsaturated monomers can be included as diluents and modifiers, as described above in conjunction with the polymerization of acrylic polymers.

[0070] Suitable monomers in the second monomer mixture may have exemplary formulas (VI), (VII), (VIII), and (IX):

[0071]

[0072] wherein R is H or an alkyl group, and R1 is an alkyl, aryl or silyl group.

[0073] The second monomer mixture used to polymerize the acidic acrylic emulsifier core polymer can have a weight percentage of the optional acrylate monomer from 30 wt.%, 40 wt.%, or 50 wt.%, to 70 wt.%, 80 wt.%, or 90 wt.%, or within any range using any two of the foregoing as endpoints, such as 30 wt.% to 90 wt.%, 40 wt.% to 80 wt.%, or 50 wt.% to 70 wt.%, where the wt.% is based on the total weight of the second monomer mixture.

[0074] The second monomer mixture can have a weight percentage of the optional non-acylated unsaturated monomer from 0 wt.%, 10 wt.%, 20 wt.%, 30 wt.%, or 35 wt.%, to 60 wt.%, 70 wt.%, 80 wt.%, or 90 wt.%, or in any range using any two of the foregoing as endpoints, such as 0 wt.% to 90 wt.%, 10 wt.% to 80 wt.%, 20 wt.% to 70 wt.%, 30 wt.% to 60 wt.%, or 40 wt.% to 50 wt.%, where the wt.% is based on the total weight of the second monomer mixture.

[0075] The monomers used for the second polymerization may also include monomers containing hydroxyl groups, which can be used to provide crosslinking functionality in the polymer product. The monomers containing hydroxyl groups may be hydroxyl functional acrylates, such as hydroxyethyl acrylate, hydroxypropyl acrylate, 2-hydroxybutyl acrylate, 4-hydroxybutyl acrylate, acrylates of polyethylene glycol, acrylates of polypropylene glycol, glyceryl monoacrylate, etc., and the corresponding methacrylates described above. The amount of the monomers containing hydroxyl groups included in the second monomer mixture may be 0 to 10 weight %.

[0076] Because the core is relatively hydrophobic, it is not necessary to include monomers containing acid groups in the second stage, but a small amount of acid functionality may be present. It is sometimes believed that a small amount of acid in the core is conducive to the polymerization process. Monomers containing acid groups may be selected from any one of those monomers used for shells. Based on the gross weight of monomers in the second monomer mixture, monomers containing acid groups may be present in the second monomer mixture in an amount of 0wt.%, 2wt.%, or 4wt.% to 6wt.%, 8wt.%, or 10wt.%, or in any range using any two of the aforementioned as endpoints, such as 0wt.% to 10wt.%, 2wt.% to 8wt.%, or 4wt.% to 6wt.%.

[0077] The acidic acrylic emulsifier 12 can be polymerized in the absence of a chain transfer agent to produce a hybrid core-shell acrylic 14. Chain transfer agents are compounds used to control chain length during synthesis to achieve certain mechanical and processing properties.

[0078] Optionally, the core 12, the shell 11 or both can be cross-linked. It is particularly advantageous to include a combination of unsaturated epoxy compounds and multifunctional vinyl compounds in the core. Multifunctional vinyl cross-linking monomers or "linking monomers" can include allyl methacrylate, ethylene glycol dimethacrylate, trimethylolpropane triacrylate, triallyl cyanurate, etc. in the monomer feed. Based on the total weight of the monomers in the second monomer mixture, the multifunctional vinyl linking monomer can be 0wt.%, 0.1wt.%, or 1wt.% to 4wt.%, 6wt.%, or 8wt.%, or in any range using any two of the foregoing as endpoints, such as 0wt.% to 8wt.%, 0.1wt.% to 6wt.%, or 1wt.% to 4wt.% The amount is included in the second monomer mixture. Unsaturated epoxy linking monomers can include glycidyl acrylate, glycidyl methacrylate and allyl glycidyl ether.

[0079] The second monomer mixture can have a weight percentage of unsaturated epoxy-linked monomers of 0 wt.%, 0.5 wt.%, 1 wt.%, 1.5 wt.%, or 2 wt.%, to 2.5 wt.%, 3 wt.%, 3.5 wt.%, 4 wt.%, 4.5 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, or 8 wt.%, or in any range using any two of the foregoing as endpoints, such as 0 wt.% to 8 wt.%, 0.5 wt.% to 7 wt.%, 1 wt.% to 6 wt.%, 1.5 wt.% to 5 wt.%, 2 wt.% to 4.5 wt.%, 2.5 wt.% to 4 wt.%, or 3 wt.% to 3.5 wt.%, where the wt.% is based on the total weight of the second monomer mixture. The co-reaction of the acid groups with the epoxy groups produces crosslinked particles.

[0080] The second monomer mixture can contain a second linking monomer type that can be optionally included, such as an alkoxy acrylamide, including N-butoxymethyl acrylamide. The second monomer mixture can have a second linking monomer weight percentage of 0 wt.%, 5 wt.%, or 10 wt.% to 15 wt.%, 20 wt.%, 25 wt.%, or 30 wt.%, or in any range using any two of the foregoing as endpoints, such as 0 wt.% to 30 wt.%, 5 wt.% to 25 wt.%, 10 wt.% to 20 wt.%, or 15 wt.% to 20 wt.%, where the wt.% is based on the total weight of the second monomer mixture.

[0081] The two or more polymers may be cross-linked together via chemical bonding, such as via cross-linking covalent bonds, between the epoxy-functional monomer component of the first polymer and the acid-functional monomer components of the shell and core polymers.

[0082] Alternatively, or in addition to the crosslinks formed by chemical bonding discussed above, the core and shell polymers can be connected via non-covalent interactions (non-chemical bonding) between the monomer components of the shell and core polymers, such as via van der Waals forces, dipole-dipole interactions, ionic interactions, or hydrogen bonding.

[0083] The resulting film-forming resin may be a hybrid acrylic core-shell polymer 14 of the exemplary formula (X):

[0084]

[0085] wherein R is H or an alkyl group, and R1 is an alkyl, aryl or silyl group.

[0086] In formula (X1), the dotted line indicates that the acid added to the epoxy ring can be located on any carbon of the epoxy ring, where the acid is usually added to the epoxy carbon with the least steric hindrance, so that the actual resulting chemical structure of the hybrid acrylic core-shell polymer 14 can be represented by formula (X2).

[0087] The hybrid acrylic core-shell polymer 14 can be formulated into a hybrid core-shell emulsion coating composition 100a by adding additives such as fillers, pigments, crosslinkers, and rheology modifiers as described below. The coating 100a can be a flexible heat-resistant coating.

[0088] The coating composition can include the hybrid acrylic core-shell polymer 14 in an amount of 0 wt.%, 1.0 wt.%, 1.5 wt.%, or 2 wt.%, to 2.5 wt.%, 3.0 wt.%, 3.8 wt.%, or 4.0 wt.%, or in any range using any two of the foregoing as endpoints, such as 1 wt.% to 4.0 wt.%, 1.0 wt.% to 3.8 wt.%, 1.5 wt.% to 3.0 wt.%, or 2.0 wt.% to 2.5 wt.%, where the wt.% is based on the total weight of the coating composition ("wet" weight).

[0089] The coating compositions provided by the present disclosure may include a hybrid acrylic core-shell polymer 14 in an amount of 0 wt.%, 1 wt.%, 10 wt.%, 15 wt.%, or 20 wt.%, to 25 wt.%, 30 wt.%, 35 wt.%, or 40 wt.%, or within any range using any two of the foregoing as endpoints, such as 1 wt.% to 40 wt.%, 10 wt.% to 35 wt.%, 15 wt.% to 30 wt.%, or 20 wt.% to 25 wt.%, wherein the wt.% is based on the total weight of the solid components of the coating composition (the "dry" weight).

[0090] b. Pathway 20

[0091] If via Figure 1 As shown in the pathway 20 of the present invention, a silicone acrylic emulsion coating composition can be formed. The silicone acrylic emulsion coating composition can include an aqueous medium, a neutralizer, and emulsion particles. To form the emulsion particles, the acidic acrylic polymer 11 discussed above can be neutralized to produce an aqueous acidic acrylic emulsion 22 in a manner also described in conjunction with the acidic acrylic emulsifier 12 of pathway 10. The resulting acrylic emulsifier 22 can be blended with a film-forming resin, which can be a siloxane polymer, such as a silicone-modified organic hydrophobic polymer, and emulsified in water to form an emulsion 24.

[0092] The silicone-modified polymers may be solid organosiloxane-based polymers such as methyl silicone resins, phenyl silicone resins or methyl-phenyl silicone resins, which are generally thermosetting compositions that can provide a range of mechanical properties, ranging from soft and rubbery to hard and brittle.

[0093] The organoalkoxysilane can be grafted onto free hydroxyl groups of a polymer such as a hydrophobic polymer. For example, the hydrophobic polymer can have an acid value of less than 20 mg KOH, less than 15 mg KOH, or less than 10 mg KOH, wherein the acid value can be determined according to ASTM D4662-15 (2020) using a Metrohm 798MPT Titrino automatic titrator manufactured by Metrohm AG.

[0094] Examples of suitable hydrophobic polymers include acrylic polymers, epoxy polymers, and polyurethane polymers, as well as polyester polymers, as described in more detail below.

[0095] The silicone-containing polymer can be reacted with or grafted onto a hydrophobic polymer to provide a silicone-modified polymer.

[0096] Exemplary organoalkoxysilanes have the formula:

[0097] R x Si(OR') 4-x

[0098] wherein R is one or more moieties independently selected from linear, branched or cyclic alkyl and aryl, including, for example, cyclohexyl and / or phenyl; R′ is methyl, ethyl, propyl or alkyl; and x is 0, 1, 2 or 3.

[0099] The degree of crosslinking in turn depends on the nature of the organosiloxane units used in the composition.As shown in the table below, organosiloxanes can be described according to the degree of oxygen substitution or functionality on the central silicone.

[0100] Table 1: Organosiloxane oxygen substitution

[0101]

[0102] Generally, compositions containing higher fractions of T (trifunctional) and Q (tetrafunctional) units show a higher degree of crosslinking.

[0103] In some instances, R is a C6 aryl or a straight or branched alkyl group having as few as 1, 2, 3 or as many as 4, 5, 6 or more carbon atoms or any other range combination of these endpoints. In an example, R is selected from methyl, ethyl, propyl and phenyl. In some instances, x is at least 1 and less than 4.

[0104] In some examples, the organoalkoxysilane comprises at least one organoalkoxysilane selected from methyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, dimethyldimethoxysilane, trimethylmethoxysilane, trimethylethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, cyclohexyltrimethoxysilane, or a combination of the foregoing.

[0105] In some examples, the organoalkoxysilane is a functionalized siloxane such as 3-aminopropyltriethoxysilane, (3-glycidoxypropyl)trimethoxysilane, and allyltrimethoxysilane. One suitable organoalkoxysilane is RSN-5314 resin, available from Dow Corning of Midland, MI.

[0106] Other suitable silicone materials are silsesquioxanes having the formula:

[0107] [RSiO3 / 2] n .

[0108] As discussed above, organosiloxane polymers can be grafted onto hydrophobic polymers, such as polyesters, to produce silicone-modified polymers of formula (XI):

[0109]

[0110] wherein R2 is an OH functional polymer, R3 is an H group, OH, an alkyl, aryl or alkoxy group, m1 is a first organosiloxane monomer, m2 is a second organosiloxane monomer, n is an organosiloxane monomer to which the polymer and additional organosiloxane monomer are bonded, and X is a bonding site for further polymer / silicone modified polymer grafting.

[0111] The silicone resin may be formed by combining two or more of the silicone-modified polymers of formula (XI) at the binding site X. The silicone resin may be blended with an acidic acrylic emulsifier to form a silicone acrylic polymer.

[0112] The film-forming resin of formula (XI) (silicone-modified polymer / silicone resin) can be blended with an acid-rich acrylic emulsifier to form a silicone acrylic polymer.

[0113] The resulting silicone acrylic polymer can be emulsified in water to form a silicone acrylic emulsion 24 of formula (XII):

[0114]

[0115] wherein R is H or an alkyl group, and R1 is an alkyl, aryl or silyl group.

[0116] The silicone acrylic emulsion 24 may be formulated into a silicone acrylic emulsion coating composition 100b by adding additives such as fillers, pigments, crosslinking agents, and rheology modifiers. The coating 100b may be a flexible heat-resistant coating.

[0117] The coating composition can include an amount of silicone acrylic emulsion 24 in an amount from 10 wt.%, 20 wt.%, or 30 wt.%, to 50 wt.%, 60 wt.%, or 70 wt.%, or in any range using any two of the foregoing as endpoints, such as 10 wt.% to 70 wt.%, 20 wt.% to 60 wt.%, or 30 wt.% to 50 wt.%, wherein the wt.% is based on the total weight of the coating composition ("wet" weight).

[0118] The coating compositions provided by the present disclosure may include a weight percentage of a silicone acrylic emulsion 24, or residues of such emulsions in a cured coating, in an amount from 10 wt.%, 20 wt.%, or 30 wt.%, to 50 wt.%, 60 wt.%, or 70 wt.%, or within any range using any two of the foregoing as endpoints, such as 10 wt.% to 70 wt.%, 20 wt.% to 60 wt.%, or 30 wt.% to 50 wt.%, wherein the wt.% is based on the total weight of the solid components of the coating composition ("dry" weight).

[0119] 1. Formation of polyester polymer

[0120] The polyester polymer may include an alcohol component including a diol and a polyol, an acid component including terephthalic acid and isophthalic acid, wherein the terephthalic acid and isophthalic acid are present in a desired molar ratio. The polyester polymer may include carboxylic acid functional groups, a weight average molecular weight (MW) of at least 5000 Daltons (Da), and an acid value (AV) of 40 to 65.

[0121] The polyester polymer can be film-forming and have reactive substituent groups, such as end groups, which can react with other molecules to modify the polymer as described below. For example, polyester polymers having reactive groups are referred to as "functionalized" polyesters. The functional group can be a carboxyl (COOH) group or a hydroxyl (OH) group, which can be the end group of the polymer chain, so that the polymer can be hydroxyl-terminated. In this way, the polyester polymer can be "functionalized" with hydroxyl groups and carboxyl groups, which helps to make the polymer water-soluble by neutralization with a corresponding base such as dimethylethanolamine (DMAE), so that the polyester polymer can be formulated in a water-based coating system.

[0122] The polyester polymer may comprise an alcohol component including diols and polyols, an acid component including two chemically different diacids, and free carboxylic acid functional groups. It has been surprisingly found that the ratio of diacids, such as isophthalic acid to terephthalic acid, can improve the balance of flexibility, elongation and toughness of the polymer coating. The appropriate ratio also produces a high glass transition temperature.

[0123] The polyester polymer may have a structure represented by the following formula (XIII):

[0124]

[0125] Where n=2.

[0126] The polyester polymer can be prepared in two consecutive reaction stages. In the first stage, an alcohol component including a diol component and a polyol component can be reacted with an acid component including two chemically different diacids in the presence of an end-capping agent in the presence of a catalyst. In the second stage, the polyester polymer of the first stage can be reacted with an anhydride to install a free carboxylic acid. After the second stage, the mixture can be diluted with a solvent. The mixture can then be neutralized by adding a base.

[0127] In the first stage, the polymer can be formed by reacting one or more diols, such as ethylene glycol, one or more polyols, such as trimethylolpropane, two chemically different diacids, such as isophthalic acid and terephthalic acid, and an endcapping agent, such as benzoic acid, in the presence of a catalyst, such as titanium (IV) butoxide.

[0128] During the first stage, the reaction temperature can be any value ranging from 80°C or more, 100°C or more, 120°C or more, 140°C or more, 160°C or more, or 180°C or less, 200°C or less, 220°C or less, or 240°C or less, using any other ranges of these endpoints, such as 80°C to 240°C, 120°C to 200°C, or 160°C to 180°C. In addition, water can be removed from the mixture until the desired AV (acid value) is reached. For example, water can be removed until the AV is less than 20, less than 15, less than 10, or greater than 5, using any other ranges of these endpoints, such as from 5 to 20, from 5 to 15, or from 5 to 10. As used herein, "acid value (AV)" is defined as the number of milligrams of potassium hydroxide (KOH) required to neutralize one gram of chemical.

[0129] During the first stage of the reaction, a catalyst can be used to promote the formation of the ester bond. The catalyst can be a tin-based or titanium-based catalyst. For example, suitable catalysts can include titanium (IV)-based catalysts and tin (IV)-based catalysts, such as titanium (IV) butoxide and dibutyltin dilaurate.

[0130] During the first stage, the catalyst can be present in an amount of 0.01 wt.% or greater, 0.05 wt.% or greater, or 0.1 wt.% or less, 0.2% or less, or any other range using these endpoints, such as 0.01 wt.% to 0.2 wt.%, or 0.05 wt.% to 0.1 wt.%, based on the total weight of the polyester.

[0131] In the second stage, an anhydride, such as trimellitic anhydride, can be added to the polymer to react with free hydroxyl groups, such as terminal hydroxyl groups, to end-cap the polymer. After the second stage, the mixture can be diluted with a solvent, such as ethylene glycol monobutyl ether. The mixture can be further treated with an amine base, such as dimethylethanolamine (DMEA) under neutralization conditions.

[0132] During the second stage, the reaction temperature can be any value ranging from 130°C or more, 140°C or more, 150°C or more, 160°C or more, 170°C or less, 180°C or less, 190°C or less, 200°C or less, 210°C or less, or any other range using these endpoints, such as 130°C to 210°C, 140°C to 190°C, or 150°C to 180°C.

[0133] After the second stage, for example, AV can be any value in the range of 40 to or 65, such as 40 or greater, 45 or greater, 50 or greater, or 55 or less, 60 or less, 65 or less, or any other range using these endpoints, such as 40 to 65, 50 to 60, or 45 to 55.

[0134] After the second stage, the mixture can be diluted to the desired solids content.

[0135] Suitable solvents that can be used include, but are not limited to, ethylene glycol monobutyl ether, diethylene glycol monomethyl acetate, propylene glycol monomethyl ether acetate, and mixtures of esters, such as Estasol obtained from Chemoxy International, Middlesbrough, UK. The mixture can be neutralized by adding a base. Amine bases can be used for neutralization. Suitable amine bases include, but are not limited to, dimethylethanolamine (DMEA), 2-amino-2-methyl-1-propanol, and ammonia.

[0136] In the polyester polymer, the weight percent of a glycol such as ethylene glycol, or the combined weight percents thereof where more than one glycol is used, as a percentage of the total polyester polymer weight, may comprise 8.0% or greater, 9.0% or greater, 10.0% or greater, 11.0% or greater, 12.0% or greater, 12.5% ​​or greater, or 13.0% or less, 13.5% or less, 14.0% or less, 15.0% or less, or 16% or less. The glycol or more than one glycol may be present in the composition in a weight percent of the total polymer ranging from 8.0% to 16.0%, such as 12.0% to 13.5%, 12.5% ​​to 13.0%, or any other combination of ranges using these endpoints.

[0137] In the polyester polymer, the weight percentage of a polyol, such as trimethylolpropane, or the combined weight percentages thereof using more than one polyol, as a percentage of the total polyester polymer weight can comprise 20% or more, 22% or more, 24% or more, 25% or more, 26% or more, 27% or more, 28% or more, 29% or more, or 30% or less, 31% or less, 32% or less, 33% or less, 34% or less, 35% or less, 37% or less, or 40% or less. The polyol or more than one polyol can be present in the composition in a weight percentage of the total polymer ranging from 20% to 40%, such as 29% to 33%, 28% to 32%, or any other combination of ranges using these endpoints.

[0138] In the polyester polymer, the molar ratio of diol to polyol, such as ethylene glycol to trimethylolpropane, can be 0.3:1.0 or greater, 0.4:1.0 or greater, 0.5:1.0 or greater, 0.6:1.0 or greater, or 0.7:1.0 or less, 0.8:1.0 or less, 0.9:1.0 or less, or any other range combination using these endpoints.

[0139] In the polyester polymer, the weight percent of the first diacid, such as terephthalic acid, as a percentage of the total polyester polymer weight can comprise 19.0% or more, 19.5% or more, 20.0% or more, 20.5% or more, 21.0% or more, 21.5% or more, 22.0% or more, 22.5% or more, or 23.0% or less, 23.5% or less, 24.0% or less, 24.5% or less, 25.0% or less, 25.5% or less, or 26.0% or less. The first diacid can be present in the composition in a weight percent of the total polymer ranging from 19.0% to 26.0%, 21.0% to 24.0%, or any other range combination using these endpoints.

[0140] In the polyester polymer, the weight percent of the second diacid, such as isophthalic acid, as a percentage of the total polyester polymer weight can comprise 23.0% or more, 23.5% or more, 24.0% or more, 24.5% or more, 25.0% or more, 25.5% or more, 26.0% or more, 26.5% or more, or 27.0% or less, 27.5% or less, 28.0% or less, 28.5% or less, 29.0% or less, 29.5% or less, or 30.0% or less. The second diacid can be present in the composition in a weight percent of the total polymer ranging from 23.0% to 30.0%, 25.5% to 28.0%, 26.0% to 27.0%, or any other range combination using these endpoints.

[0141] In the polyester polymer, the molar ratio of the first diacid to the second diacid (such as terephthalic acid to isophthalic acid) can be 0.6:1.0 or greater, 0.7:1.0 or greater, or 0.8:1.0 or less, 0.9:1.00 or less, using any range combination of these endpoints. For example, the ratio of terephthalic acid to isophthalic acid can be 0.86:1.00. The aforementioned ratio of terephthalic acid to isophthalic acid helps balance the desired properties of the polyester polymer, which include flexibility, elongation, and toughness, while providing a high glass transition temperature.

[0142] In the polyester polymer, the weight percentage of the end-capping agent, such as benzoic acid, as a percentage of the total polyester polymer weight can include 1.0% or greater, 1.5% or greater, 2.0% or greater, or 2.5% or less, 3.0% or less, 3.5% or less, or 4.0% or less. The end-capping agent can be present in the composition in a weight percentage of the total polymer ranging from 1.0% to 4.0%, 2.0% to 2.5%, or any other range combination using these endpoints.

[0143] In the polyester polymer, the weight percent of anhydride, such as trimellitic anhydride, as a percentage of the total polyester polymer weight may comprise 5.0% or greater, 5.5% or greater, 6.0% or greater, or 6.5% or less, 7.0% or less, or 7.5% or less. The anhydride may be present in the composition as a weight percent of the total polymer in the range of 5.0% to 7.5%, 5.5% to 7.0%, or any other range combination using these endpoints.

[0144] For example, the average molecular weight (MW) of a polyester polymer may be 5000.

[0145] Dalton (Da) or more, 7000 Da or more, 8000 Da or more, 10,000 Dalton (Da) or more, 12,000 Da or more, or 14,000 Da or less, 16,000 Da or less, 18,000 Da or less, 20,000 Da or less, or any range combination using these endpoints, such as 5000 Da to 20,000 Da, 10,000 Da to 18,000 Da, or 12,000 Da to 16,000 Da.

[0146] For example, the glass transition temperature (Tg) of the polyester polymer can be 60°C or more, 70°C or more, 80°C or more, 85°C or less, 90°C or less, 95°C or less, or any range combination using these endpoints, such as 60°C to 95°C, or 70°C to 90°C.

[0147] Once the polymer is fully crosslinked, the Tg of the polyester polymer can be

[0148] 80° C. or more, 85° C. or more, 90° C. or more, 95° C. or more, 100° C. or more, 110° C. or more, or 115° C. or less, 120° C. or less, 125° C. or less, 130° C. or less, 135° C. or less, or any range combination using these endpoints, such as 60° C. to 135° C., 80° C. to 125° C., or 95° C. to 120° C. For example, the Tg of a fully crosslinked polyester polymer can be 120° C.

[0149] c. Pathway 30

[0150] like Figure 1 As shown in the route 30 of the present invention, a silicone acrylic emulsion coating composition can be formed. The silicone acrylic emulsion coating composition can include an aqueous medium, a neutralizer, and emulsion particles. In order to form the emulsion particles, the acidic acrylic shell polymer 11 can be blended with a silicone modified polymer or a silicone resin (film-forming resin) to produce an acrylic silicone modified polymer blend 32. The silicone modified polymer / silicone resin can have the formula (XI) formed by the process described in the route 20.

[0151] The resulting acrylic silicone modified polymer blend 32 can be emulsified in water to produce a silicone acrylic emulsion 34 of formula (XII), similar to Figure 1 Silicone acrylic emulsion 24 of route 20.

[0152] The silicone acrylic emulsion 34 can be formulated into a silicone acrylic emulsion coating composition 100b by adding additives such as fillers, pigments, crosslinkers, and rheology modifiers, as described above with respect to route 20. The coating 100b can be a flexible heat-resistant coating.

[0153] ii. Solvent-based coating compositions

[0154] d. Pathways 40a and 40b

[0155] like Figure 1 As shown in pathways 40a and 40b, an acrylic / silicone polymer blend coating composition 100c can be formulated from an acrylic / silicone polymer blend 42.

[0156] The acrylic / silicone polymer blend 42 can be formed by blending the acidic acrylic shell polymer 11 with a silicone modified polymer or silicone resin. The silicone modified polymer / silicone resin can be a film-forming resin of formula (XI) formed by the process described in route 20.

[0157] Alternatively, the acrylic / silicone polymer blend 42 may be formed by neutralizing the acidic acrylic polymer 11 to produce an aqueous acid-rich acrylic emulsion 12, which is then blended with a silicone-modified polymer or silicone resin.

[0158] The acrylic / silicone modified polymer blend 42 can be directly formulated into an acrylic / silicone modified polymer coating composition 100c by adding additives such as fillers, pigments, crosslinkers, and rheology modifiers as described below. The coating 100c can be a flexible heat resistant coating.

[0159] The acrylic / silicone modified polymer coating composition 100c can contain an amount of film-forming resin in an amount from 50 wt.%, 60 wt.%, or 70 wt.% to 80 wt.%, 85 wt.%, or 90 wt.%, or in any range using any two of the foregoing as endpoints, such as 50 wt.% to 90 wt.%, 60 wt.% to 85 wt.%, or 70 wt.% to 80 wt.%, where the wt.% is based on the total weight of the coating composition ("wet" weight).

[0160] The acrylic / silicone modified polymer coating composition 100c can contain an amount of film-forming resin, or residues of such film-forming resin in the cured coating, in an amount from 50 wt.%, 60 wt.%, or 70 wt.% to 80 wt.%, 85 wt.%, or 90 wt.%, or within any range using any two of the foregoing as endpoints, such as from 50 wt.% to 90 wt.%, 60 wt.% to 85 wt.%, or 70 wt.% to 80 wt.%, wherein the wt.% is based on the total weight of the solid components of the coating composition (the "dry" weight).

[0161] B. Additives

[0162] The water-based 100a, 100b and solvent-based 100c coating compositions may contain additives such as fillers, pigments, wetting agents, rheology modifiers, dispersants, crosslinking agents, and toughening agents.

[0163] i. Filling

[0164] One or more fillers in the form of inorganic particulate materials may optionally be added to increase thermal conductivity through the coating 100a, 100b, 100c and / or for reinforcement to improve hardness. Additionally, fillers may increase the wear resistance of the coating when applied to a substrate.

[0165] A suitable heat-resistant filler is alumina (aluminum oxide, Al2O3), and other suitable heat-resistant fillers include titanium dioxide (TiO2), barium sulfate (BaSO4), polyetheretherketone (PEEK), polyethersulfone (PES) and silicon carbide (SiC), magnesium fluoride (MgF2), barite powder (BF or barium sulfate) and calcium fluoride (CaF2).

[0166] The coating compositions provided herein may include fillers in an amount of 0 wt.%, 1.0 wt.%, 1.5 wt.%, or 2 wt.% to 2.5 wt.%, 3.0 wt.%, 3.8 wt.%, or 4.0 wt.%, or in any range using any two of the foregoing as endpoints, such as 1 wt.% to 4.0 wt.%, 1.0 wt.% to 3.8 wt.%, 1.5 wt.% to 3.0 wt.%, or 2.0 wt.% to 2.5 wt.%, wherein the wt.% is based on the total weight ("wet" weight) of the coating composition.

[0167] The coating compositions provided by the present disclosure may include fillers in an amount of 0 wt.%, 1 wt.%, 10 wt.%, 15 wt.%, or 20 wt.%, to 25 wt.%, 30 wt.%, 35 wt.%, or 40 wt.%, or within any range using any two of the foregoing as endpoints, such as 1 wt.% to 40 wt.%, 10 wt.% to 35 wt.%, 15 wt.% to 30 wt.%, or 20 wt.% to 25 wt.%, wherein the wt.% is based on the total weight of the solid components of the coating composition ("dry" weight).

[0168] ii. Pigments

[0169] In order to provide an aesthetically pleasing appearance to the coating, one or more pigments may be used. Suitable pigments include metal oxides, ochres, minerals, synthetic pigments or pigments of biological origin. The pigments may be used as powders or liquids and may be formulated into pastes.

[0170] Based on the "dry" or solid weight of the coating composition after application to a substrate and then curing, the coating compositions provided by the present disclosure can include pigments in an amount of 3 wt.%, 5 wt.%, 7 wt.%, 9 wt.%, or 11 wt.%, to 13 wt.%, 15 wt.%, 17 wt.%, or 20 wt.%, or within any range using any two of the foregoing as endpoints, such as 3 wt.% to 20 wt.%, 5 wt.% to 17 wt.%, 7 wt.% to 15 wt.%, or 9 wt.% to 11 wt.%, where the wt.% is based on the total weight of the "dry" coating composition.

[0171] iii. Cross-linking agent

[0172] The present coating composition 100a, 100b, 100c may also include at least one optional crosslinking agent to form crosslinks between base resin polymer chains, thereby improving the flexibility of the present coating. Typically, the crosslinking agent will react through functionalized reactive groups on the polymer chains, such as carboxyl or hydroxyl groups.

[0173] The crosslinking agent for the carboxyl-functional base resin may be a metal salt such as zinc ammonium carbonate or zinc oxide.

[0174] The crosslinking agent may be an amino-based crosslinking agent or a melamine crosslinking agent, such as a melamine-type crosslinking agent of formula (XIV):

[0175]

[0176] In one melamine-type crosslinking agent of the above formula, R may be H or a C1-C6 alkyl group.

[0177] The crosslinking agent may be a highly methylated monomeric melamine crosslinking agent of formula (XV):

[0178]

[0179] Wherein R1 to R6 are each selected from -H, -CH2OH, -CH2OR7, and may be the same or different, wherein R7 is a C1 to C5 alkyl group. R7 may be selected from -CH3 or -C4H9 R1 to 5 may also each be -CH2OCH3. A suitable crosslinking agent is hexamethoxymethylmelamine, such as Cymel 303, available from Allnex SA of Brussels, Belgium.

[0180] Other crosslinking agents may be of the glycoluril type of formula (XVI):

[0181]

[0182] In the glycoluril type crosslinking agent of the above formula, R may be a C1-C6 alkyl group.

[0183] Other crosslinking agents may be of the urea type of formula (XVII):

[0184]

[0185] In the urea-type crosslinking agent of the above formula, R may be a methyl group or a butyl group, and R2 may be a H, a C1-C6 alkyl group or an alkoxy group.

[0186] Still further cross-linking agents may be of the benzoguanamine type of formula (XVIII):

[0187]

[0188] In the benzoguanamine crosslinker of the above formula, R may be H, methoxyethyl or ethoxyethyl.

[0189] Further cross-linking agents include isocyanates, carbodiimides and dicyandiamide, among others.

[0190] The amount of crosslinker can comprise 0 wt.% or more, 0.2 wt.% or more, 0.8 wt.% or more, or 1 wt.% or less, 2 wt.% or less, or 10 wt.% or less, or any other range combination using any two of the foregoing endpoints, such as 0 wt.% to 10 wt.%, 0.2 wt.% to 2 wt.%, or 0.8 wt.% to 1 wt.%, based on the "wet" weight of the coating composition (i.e., the composition comprising water and organic solvent (if present)) prior to application to a substrate and subsequent curing.

[0191] The amount of crosslinker can comprise 0 wt.% or more, 0.2 wt.% or more, 0.8 wt.% or more, or 2 wt.% or less, 5 wt.% or less, or 10 wt.% or less, 20 wt.% or less, or any other range combination using these endpoints, such as 0 wt.% to 20 wt.%, 0.2 wt.% to 10 wt.%, or 0.8 wt.% to 5 wt.%, based on the "dry" or solid weight of the coating composition after application to a substrate and then curing.

[0192] IV. Substrate, Application and Curing of Coating Compositions

[0193] Waterborne and solventborne coating compositions can be applied to a substrate by spraying, roller coating, roll coating, screen printing, curtain coating, or dipping, and then thermally cured under various time / temperature conditions depending on the application.

[0194] A. Base material

[0195] The coating composition can be applied to the surface of the substrate. The substrate can be untreated or pretreated. The pretreatment of the substrate can include primer coating, etching, anodizing and other suitable forms of priming. Suitable substrates can include metals, ceramic materials, plastics, composite materials and minerals. Suitable metals can include stainless steel, aluminum and carbon steel. Suitable ceramic materials can include glass, such as borosilicate glass, enamel, various fired clays and other refractory materials. Suitable plastics and composite materials can include high melting point plastics and composite materials, such as plastics with melting points higher than the curing temperature of the coating formulation, including polyester, polypropylene, ABS, polyethylene, carbon fiber epoxy composites and glass fiber epoxy composites. Suitable minerals can include mica, basalt, aluminum oxide, silicon dioxide and wollastonite, marble and granite.

[0196] The substrate may be part of a pan or other cookware item. Figure 2A , the cookware article 200 is shown in the form of a pan, which generally includes a circular bottom wall 202, an annular side wall 204 and a handle 206. The cookware article 200 is generally a metal or metal alloy, such as stainless steel, aluminum and carbon steel, but may also be a ceramic material, plastic or a composite material.

[0197] The bottom wall 202 and the side wall 204 include an inner surface or food contact surface 208 facing the food to be cooked, and an opposite outer surface or heat contact surface 220 which, in use, faces, is adjacent to or contacts a heat source or heating element 222. Figure 2B As shown, the cookware article 200 may include an interior coating 224 on at least a portion of respective interior surfaces thereof including at least a portion or all of the bottom wall 202 and / or side walls.

[0198] In this manner, the coating composition of the present invention can be used as an interior coating or an exterior coating. Although the cookware article 200 is shown as a frying pan, the present coating composition can also be used to form a coating for the cooking surface of other cookware articles, such as pots, shallow pots, pans, etc., as well as bakeware articles or other cooking articles that are exposed to heat during use. In addition, the present coating composition can be used to form a coating on the non-cooking surface of other cooking utensils, such as a grill.

[0199] The present coating compositions may also be used to coat non-cookware articles, such as rollers, molds, ducts, and fasteners, which require non-stick or release properties and / or which are exposed to temperatures above ambient during use.

[0200] B. Application

[0201] The coating compositions 100a, 100b, 100c can each be applied using the following methods.

[0202] i. Spraying

[0203] The water-based and solvent-based coating compositions disclosed herein can be applied to a substrate using spraying. Spraying involves loading the coating composition into an apparatus, wherein the coating composition is then forced through a nozzle so that the composition is made into a fine aerosol spray. The spray is then directed directly to the substrate to obtain a uniform coating.

[0204] After spraying the substrate with the coating composition, the coating composition can be initially quickly cured at as low as 50° C. or as high as 120° C. to remove water. The spray composition can also be cured at a temperature of 170° C., 190° C., or 210° C. to 230° C., 250° C., or 280° C. for a period of 3 min, 7 min, or 11 min to 13 min, 14 min, or 15 min, such as 3 minutes at 274° C., 10 minutes at 200° C., or 15 minutes at 170° C.

[0205] ii. Roller coating

[0206] Roll coating is the process of printing a composition onto a substrate using roll-to-roll technology. Roll-to-roll technology typically uses a single or multiple rollers that wrap the substrate around and through a roller covered in the print composition. As the substrate moves along the rollers, the composition is applied to the substrate.

[0207] The coating compositions disclosed herein can be applied using roller coating techniques. The coating compositions can be rapidly cured at temperatures as low as 50°C or as high as 120°C to remove water. The coating compositions can also be cured at 200°C for 10 minutes, at 170°C for 15 minutes, or at 274°C for 3 minutes.

[0208] iii. Roller coating

[0209] Roll coating is the process of applying a coating composition to a substrate using a reverse roller technique. The web can be passed through a coating head using a roll-to-roll technique using multiple rollers. The rollers rotate in the opposite direction of the web and apply the coating composition to the substrate. As the substrate moves along the rollers, the coating composition can be applied to the substrate.

[0210] The coating compositions disclosed herein can be applied using a roll coating technique. The acrylic polymer, silicone / organic modified silicone composition can be further cured at 100°C to remove the solvent. The roll-coated acrylic polymer, silicone / organic modified silicone composition can also be cured at a peak metal temperature of 360°C to 400°C for 10 to 15 seconds.

[0211] iv. Screen printing coating

[0212] Screen printing coating is the process of printing a composition onto a substrate using a grid technique. The screen printing technique can use single or multiple applications to apply a coating onto a grid covered with a coating composition and through the grid to the substrate. The coating composition is applied to the substrate as the substrate moves under the grid.

[0213] The coating composition disclosed herein can be applied using screen printing technology. The coating composition 100b can be further cured at as low as 50°C or as high as 120°C to remove water. The coating composition 100b can also be cured at 200°C for 10 minutes, at 170°C for 15 minutes, or at 274°C for 3 minutes.

[0214] v. Preformed and post-formed products

[0215] The coating compositions 100a, 100b, 100c can be applied to pre-formed and post-formed articles while maintaining desired properties.

[0216] A preformed article may be an article formed from a substrate and cast into the desired final shape prior to application of the coating composition.

[0217] The post-formed product can be a product formed by a substrate that has not yet reached the desired final shape. The post-formed product is coated with a coating composition and then deformed or otherwise forced to form a desired shape. An example of a process for forming a substrate into a desired shape may include a deep drawing process. Deep drawing is a process in which a substrate is deformed by mechanical action so that the substrate is formed into a specific structure. The process is performed by a punch and a die. The punch is the desired shape of the substrate. The die is a cavity whose shape matches the shape of the punch but is slightly wider. The substrate is placed on the opening of the die, and a force is applied to each end of the substrate on either side of the die cavity opening. Then, when the substrate moves into the die cavity, a force is applied to the substrate using a punch so that the substrate is forced into the die cavity to form the shape of the punch. When a lot of force is applied to the substrate, the deep drawing process may cause the substrate material to fail or any coating on the substrate to rupture. The coating composition of the present disclosure can be applied and cured to an unformed substrate and withstand the force of deep drawing or other suitable forming processes to form a final product.

[0218] V. Coating Characteristics

[0219] The cured coating compositions 100a, 100b, and 100c may be flexible and heat resistant, and exhibit other properties as discussed below.

[0220] A. Dry film thickness

[0221] Dry film thickness (DFT) is the thickness of the coating measured above the substrate.The coating composition may be a single layer or a multilayer.

[0222] The cured coating compositions 100a, 100b, 100c can have a DFT of 10 microns, 15 microns or 20 microns, 25 microns, 40 microns, or in any range using any two of the foregoing as endpoints, such as 10 microns to 40 microns, 15 microns to 25 microns, or 20 microns to 25 microns, wherein the DFT is measured according to a TM-114A electronic measuring instrument.

[0223] B. Glossiness

[0224] The gloss of a coating can be measured by comparing the specular reflectance of the coating to that of a black glass standard. This is done with an instrument that projects a beam of light onto the surface at a fixed intensity and angle and measures the amount of reflected light at an equal but opposite angle.

[0225] The coating compositions 100a, 100b, 100c of the present disclosure may have a gloss of 100 GU, 150 GU, 155 GU, or 160 GU, to 165 GU, 170 GU, or 175 GU, or in any range using any two of the foregoing as endpoints, such as 150 GU to 175 GU, 155 GU to 170 GU, or 160 GU to 165 GU, wherein the gloss is measured at 60° C. according to ASTM D523 (2018).

[0226] C.0T bending

[0227] The T bend test is carried out to find the flexibility of the composition during bending. The bending ability is important for the roller coating of the composition. The composition can be subjected to a bend ranging from 0T to 5T. According to ASTM D4145 (2018), the 0T bend test involves subjecting the composition to 180 ° of bending. The rating system as shown in Table A can be used to determine the score of the coating using the 0T bend test.

[0228] Table A: 0T bending test scores

[0229] score Coating cracking after indentation Coating removal after pulling 0T cracking after bending Pass / Fail 5 0% 0% 0% pass 4 >0-20% >0-20% >0-20% fail 3 20-40% 20-40% 20-40% fail 2 >40-60% >40-60% >40-60% fail 1 >60% >60% >60% fail

[0230] A composition was considered to have "passed" if no film or flake of the composition fell off after being subjected to a 180° bend.

[0231] D. Pencil hardness

[0232] Pencil hardness describes the ability of a coating on a substrate to resist scratching, marring or gouging. The test utilizes pencils of known hardness held at a 45 degree angle to the coated surface with a constant force to determine the hardest pencil that will not scratch the coating.

[0233] The coating compositions 100a, 100b, 100c of the present disclosure may have a pencil hardness of 3H, 4H or 5H, 6H, or in any range using any two of the foregoing as endpoints, wherein the pencil hardness is measured according to ASTM D3363 (2022) at ambient temperature, e.g., at 20°C to 23°C.

[0234] The coating compositions 100a, 100b, 100c of the present disclosure may have a pencil hardness of 2H, 3H or 4H, 5H, or in any range using any two of the foregoing as endpoints, wherein the pencil hardness is measured at 204°C according to ASTM D3363 (2022).

[0235] E. Yellowing

[0236] When the coating composition is cured, the coating may turn yellow due to the stability of the resin within the coating composition.

[0237] The stability of the resin can be tested either dynamically or isothermally. The dynamic test measures the color change after 1 hour at each temperature (230°C, 260°C and 274°C).

[0238] The isothermal test measured the color change after 1 hour, 2 hours and 4 hours at 274°C.

[0239] The color change of the coating composition can be measured using the Standard Reference Method (SRM) chart for Beer Method 6 Color from the American Association of Brewing Chemists. The SRM of a sample can be measured with light of 430 nm wavelength in a cell path length of 1 cm. The measured absorbance level is then multiplied by a factor of 12.7 to yield a color value assigned to the wort sample, as shown in Formula 1:

[0240] SRM = 12.7 × D × A 430

[0241] Typical SRM values ​​are between 1 and 40, with 1 being described as "light straw" and 40 being described as "deep black".

[0242] F.MEK double friction

[0243] The solvent resistance of the cured coating composition can be tested by using the methyl ethyl ketone (MEK) double rub (DR) test. The MEK DR test can be performed by placing the test panel on a flat table or other suitable flat, solid surface. Two sterile gauze pads can be secured to the end of a one-pound ball-pein hammer. The gauze can be secured with a rubber band so that the gauze is held tightly in place and there are four layers of gauze on the end of the hammer without wrinkles.

[0244] The gauze was saturated with an appropriate solvent for the test substrate, such as methyl ethyl ketone (MEK). The gauze was re-saturated every 25 double rubs.

[0245] Immediately wipe the coated substrate with the coating composition using saturated gauze over the test area using 2-4 inch back and forth strokes. The weight of the hammer controls the downward pressure.

[0246] The back and forth wiping may continue, counting one "double rub" for each completed forward and backward motion, until bare substrate is exposed at the center of the rubbing strip, or until 100 double rubs are achieved.

[0247] Record the number of "double rubs" as the test result. The gauze should be removed and replaced with a new one between each test sample.

[0248] The curable compositions of the present disclosure may have a solvent resistance of at least 40 MEK double rubs, at least 50 MEK double rubs, at least 70 MEK double rubs, or at least 90 MEK double rubs.

[0249] The MEK DR test can be combined with the fingernail scratch test to determine softening of the coating. The fingernail scratch test involves scratching a coating exposed to a solvent and determining the softness and recovery of the coating composition. If no coating can be scratched off after exposure to the solvent, the coating composition passes the fingernail scratch test. If the coating composition does not show wear during the MEK double rub test, but is subsequently soft enough to be scratched off during the fingernail scratch test, the coating composition may pass the MEK double rub test and then subsequently fail the fingernail scratch test.

[0250] G. Positive indentation / reverse indentation

[0251] Forward and reverse indentation tests can be performed according to ASTM D2794 (2019) and evaluated for "pass" and "fail" thresholds. In post-forming applications where the three-dimensional shape of the coated article is formed after the coating has been applied and cured, the forward / reverse impact test is used to evaluate the coating's ability to deform and stretch at a certain speed. This test can also be used in conjunction with the cross-hatch adhesion test, as described below.

[0252] H. Crosshatch Adhesion

[0253] The crosshatch adhesion test can be performed and evaluated according to ASTM 3359 Method B, BS EN 12983-1:2023 8.3.1 (1977). The crosshatch adhesion method can be used to evaluate the adhesion of the coating composition to the substrate and the brittleness of the coating. The crosshatch is used to evaluate the robustness of the coating in use. The crosshatch test method can be combined with water boiling.

[0254] I. Boil

[0255] The water boiling test may involve immersing the substrate coated with the coating composition in boiling water for one hour before other tests are performed. The water boiling test can determine whether the coating will fail prematurely once damaged.

[0256] J. Shear stability

[0257] A shear stability test can be performed to determine the ability of the coating composition to remain liquid in solution after mixing. The test can be performed by taking 200 g of the coating composition and mixing the coating using a high shear mixing blade mixer at 2000 RPM for 120 minutes. If the coating does not separate from the solution after mixing, the coating composition receives a "pass". If the coating composition does not remain liquid and separates from the solution after mixing, the coating receives a "fail".

[0258] K. Freeze-thaw stability

[0259] A freeze-thaw stability test can be performed to determine the ability of the coating composition to be repeatedly frozen and thawed without separating from the solution. The test can be performed by first measuring the viscosity of 200 g of the coating composition. The coating composition can then be placed in a sealed container and placed in a refrigerator at -15°C until the coating composition is frozen. The coating composition is kept frozen for 3 hours. Once the 3 hours have passed, the frozen coating composition can be taken out of the refrigerator and thawed naturally. During the thawing period, the coating composition is observed to check for any signs of particles separating from the solution. If the coating composition does not separate from the solution after being completely thawed, the freezing and thawing process is repeated again.

[0260] Freeze and thaw cycles are performed 5 times. After the last freeze-thaw cycle, the viscosity of the coating composition can be measured and compared to the starting viscosity of the coating composition before the freeze-thaw cycle. If the viscosity does not change, the coating composition can receive a "pass" score. If the viscosity changes after 5 cycles, or the coating composition separates from the solution before the 5 cycles are completed, the coating composition receives a "fail".

[0261] L.EU steak cycle

[0262] A steak release test can be performed to determine the ease with which a cooked steak can be removed from a substrate coated with a coating composition. The EU steak cycle test can be performed in accordance with EN 13834 on "Ovenware for use in conventional domestic ovens". The results can be evaluated using the rating scale provided in Table B below.

[0263] M.BBQ / Mustard demoulding and dyeing

[0264] The release and staining properties of the coating composition can be measured by cooking food (such as BBQ sauce, steak, eggs, mustard) in bakeware / cookware articles coated with the coating composition. Both release and staining tests can be performed according to EN13834.

[0265] To test demolding properties, food is cooked on a bakeware / cookware article coated with the coating composition, and then the ease with which the food is removed from the coated article is evaluated. The first step in evaluating the ease of food removal may be to flip the cookware / bakeware. A coating that can remove food by simply flipping it may receive a (5) rating. A second food removal evaluation may involve gently shaking the bakeware / cookware (4 and 3 ratings). And the final evaluation method for food removal may involve scraping with a spatula or other tool (2 and 1 ratings). Table B describes the ratings for demolding properties. When mustard and BBQ sauce were cooked on the coated article, articles coated with the coating composition of the present disclosure may exhibit a "pass" demolding rating.

[0266] Table B: Release Ratings for Coated Cookware / Bakeware Articles

[0267]

[0268] To test the anti-staining properties, food products were cooked on bakeware / cookware articles coated with the coating compositions, and the degree of staining of the coated articles after cooking was then evaluated as described in Table C. Articles coated with the coating compositions of the present disclosure may exhibit a staining rating of at least 3, at least 4, or at least 5 when mustard and BBQ sauce were cooked on the coated articles.

[0269] Table C: Soil Ratings for Coated Cookware / Bakeware Articles

[0270]

[0271] N. Cupping

[0272] The cupping test can be completed on a preformed article coated with one of the coating compositions in accordance with BS 3900-E4 and evaluated using BS 3900-E4. In post-forming applications where the three-dimensional shape of the coated article is formed after the coating has been applied and cured, the cupping test is used to evaluate the ability of the coating to elongate with the substrate.

[0273] The coated plate can be placed face up on the test fixture and clamped in place. The ball bearing can be lifted by the q-plate to stretch the coating. The deformation height can be set to 6mm (depending on the plate specifications and the annealing of the substrate). The coating composition can be evaluated using ASTM643 (2015).

[0274] O. Viscosity Zahn#4

[0275] The Zahn cup viscometer is a portable device for quickly measuring the viscosity of fluids such as paints, lacquers, varnishes, syrups, creams, oils, and coating compositions. The viscosity of a liquid measured by this device can be expressed in terms of a Zahn number. The Zahn number is the time (in seconds) required for a defined volume (44 mL0) of liquid to flow through the viscometer.

[0276] The coating composition of the present application can have a Zahn number of 20s, 25s, 30s, to 35s, 40s, 45s, or any range using the above values ​​as endpoints, such as 20s to 45s, 25s to 40s, or 30s to 35s.

[0277] Q. Emulsion stability

[0278] The formulation and stabilization of emulsions may be required in many of the present coating formulations. Assessments may be performed during each stage of the manufacturing process to determine the effects of time and temperature on emulsion stability and subsequently formulated emulsion coating compositions. Particle size may be assessed using dynamic light scattering, and the formation of emulsion particles and the distribution of particles over time at a given temperature may be monitored by visual assessment.

[0279] Visual assessment can be performed by observing the following characteristics in Table D:

[0280] Table D: Emulsion Stability Visual Assessment Rating

[0281] Rating Appearance observation 5 No phase separation 4 Slight signs of phase separation or precipitation 3 Phase separation that can be remixed by shaking 2 Phase separation that can be reincorporated by mixing 1 Phase separation that cannot be re-mixed

[0282] R.VOC

[0283] In many locations there are environmental standards limiting the levels of VOCs that may be present in coating compositions. VOCs are compounds with high vapor pressure (typically 10 Pa or more at 20°C) and low water solubility.

[0284] The hybrid core-shell acrylic emulsion coating composition 100a of the present disclosure can contain minimal VOC, for example, below the threshold of 3.5 lbs / gal or less of the U.S. Environmental Protection Agency (USEPA) and / or the European standard of 420 g / liter. The hybrid core-shell acrylic emulsion coating composition 100a can contain a VOC amount of less than 200 g / liter, less than 150 g / liter, less than 100 g / liter, less than 50 g / liter, less than 10 g / liter, or less than 5 g / liter, or in any range including any two of the above values ​​as endpoints, such as 5 g / liter to 200 g / liter, 10 g / liter to 150 g / liter, or 50 g / liter to 100 g / liter.

[0285] The silicone acrylic emulsion coating composition 100b can contain VOC levels that comply with VOC limits in certain states. The silicone acrylic emulsion coating 100b can contain a VOC amount of less than 370 g / liter, less than 300 g / liter, less than 250 g / liter, less than 200 g / liter, less than 150 g / liter, or less than 100 g / liter, or in any range including any two of the above values ​​as endpoints, such as 100 g / liter to 370 g / liter, 150 g / liter to 300 g / liter, or 200 g / liter to 250 g / liter.

[0286] S. Fluorinated polymers

[0287] The present coating composition may lack fluoropolymers, wherein the coating composition is fluoropolymer-free.Per- and polyfluoroalkyl substances (PFAS) are fluorinated compounds, including perfluoroalkyl acids (PFAA), such as perfluorooctanoic acid (PFOA) and / or perfluorooctane sulfonate (PFOS).

[0288] The amount of PFAS in the coating composition can be determined by liquid chromatography tandem mass spectrometry (LC-MS / MS), which can be performed using isotope dilution. The limit of quantification (LOQ) may be less than 1 part per million (ppm) or 1 part per billion (ppb).

[0289] As used herein, "PFAS-free" refers to a polymer, liquid chemical coating composition, or coating after application that includes a PFAS content of 1 ppm or less.

[0290] As used herein, "fluorine-free" refers to a polymer, liquid chemical coating composition, or applied coating that includes a fluorine content of 1.0 wt.% or less, 0.5 wt.% or less, or 0.1 wt.% or less, wherein the wt.% is based on the total weight of the coating composition.

[0291] Examples

[0292] Aspects of the present disclosure are further illustrated by reference to the following examples. It will be apparent to those skilled in the art that many modifications can be made to the materials and methods without departing from the scope of the present disclosure.

[0293] Example 1 - Formation of acrylic polymer shell

[0294] This example describes the formulation of a first polymer (acidic acrylic shell polymer) made from the following components in Table 2.

[0295] Table 2: Acrylic polymer shell formulation

[0296]

[0297]

[0298] Example 2 - Formation of Acrylic Emulsifier Core

[0299] This example describes the synthesis of an aqueous acid acrylic emulsifier core.

[0300] Table 3: Acrylic emulsifier core formulation

[0301] Example 2A Example 2B Components Weight(g) Weight(g) Polymer of Example 1A 360.0 - Polymer of Example 1C - 360.0 Styrene 134.4 134.4 Ethyl acrylate 75.4 75.4 Glycidyl Methacrylate 23.2 23.2 Methyl Methacrylate 126.8 126.8 Deionized water 1205.39 1205.39

[0302] Example 3 - Hybrid Core-Shell Acrylic Emulsion Coating Formulation

[0303] This example describes a clear hybrid core-shell acrylic emulsion coating formulation using an acidic acrylic emulsion core prepared according to Examples 2A and 2B. Table 1 below gives the wt. % of each element in the formulation.

[0304] Table 4: Hybrid core-shell acrylic emulsion coating formulation

[0305]

[0306]

[0307] The above hybrid core-shell acrylic emulsion coating composition can be applied using roller coating or spray coating techniques as described above. Once applied and cured, the coating composition has a DFT of 10 microns.

[0308] The coating applied according to ASTM D523 (2018) had a gloss of 93-170 GU at 60°C.

[0309] When subjected to 0T bend testing according to ASTM D4145 (2018), the coatings of the present disclosure obtained a passing result.

[0310] The coating has a pencil hardness of 3H at ambient temperature according to ASTM D 3363 (2022) and a pencil hardness of at least H at a temperature of 400°F (204°C) according to ASTM D3363 (2022).

[0311] Based on visual inspection, the hybrid core-shell acrylic emulsion coating composition exhibited minimal yellowing upon curing.

[0312] Example 4 - Coating Formulation Containing Fillers

[0313] This example describes the formulations of acrylic coating compositions, each of which contains a core-shell latex polymer prepared according to Example 2B and a filler. The weight percentage of each ingredient is based on the total weight ("wet" weight) of the coating composition, and the formulations are listed in Table 2 below.

[0314] Table 5: Coating formulation

[0315]

[0316]

[0317] The inclusion of filler in Example 4B had no adverse effect on the coating compared to the coating formulations of Examples 3A and 3B. However, the inclusion of filler in Example 4A did have an effect on pencil hardness.

[0318] Example 5 - Coating Composition and Application

[0319] The compositions obtained from the two-step polymerization of Examples 1 and 2 and the coating compositions of Examples 3 and 4 are hybrid core-shell acrylic emulsion coating compositions for use on bakeware, cookware, grills and other substrates. The coating compositions form a non-stick, heat-resistant, and abrasion-resistant surface on the substrate after application and curing.

[0320] Example 6 - Formation of Silicone Acrylic Emulsion

[0321] This example describes the formation of a silicone acrylic emulsion in which an acid-rich acrylic emulsifier is blended and emulsified with a silicone resin / silicone-modified polymer (film-forming resin), a neutralizer, and water.

[0322] Table 6 shows exemplary silicone modified polymers / silicone resins used as film-forming resins to produce the coating compositions of the present disclosure. The silicone polyesters were all made as discussed in Section II.Aib1. Formation of Polyester Polymers.

[0323] Table 6: Silicone modified polymers / silicone resins

[0324]

[0325]

[0326] Table 7 describes the same emulsion blend made in four different ways. Each step (1 or 2) represents a blend of components added to the mixture. Each component was added according to the indicated step (1 or 2) and mixed under high shear mixing.

[0327] Table 7: Silicone acrylic emulsion combination

[0328]

[0329] Table 8 describes the loading levels required for emulsion stability when forming silicone acrylic emulsion coating compositions in which the acid-rich acrylic polymer from Example 1 is blended with a silicone-modified polymer / silicone resin (film-forming resin), a neutralizer, and water and emulsified via the Blend C method.

[0330] Table 8: Loading levels of silicone acrylic emulsions

[0331]

[0332] Table 9 describes the emulsion stability of silicone acrylic emulsions over a period of time and under different environments.

[0333] Table 9: Emulsion stability of silicone acrylic emulsion formulations

[0334]

[0335] 1 = worst, 5 = best

[0336] Figure 3 The required particle size reduction measured by a Microtrac S2000 particle size analyzer is shown to determine the wt.% of acrylic emulsifier on the film-forming resin required to achieve and stabilize the volume distribution median (D50) and dispersity (D90-D10) determined by dynamic light scattering ISO 13320-1 when forming a silicone acrylic emulsion, wherein an acid-rich acrylic resin is blended with a film-forming resin, a neutralizer, and water and emulsified via the Blend C method. The blends of the present disclosure can have a D50 of 0.01 μm, 1 μm, or 3 μm to 5 μm, 7 μm, or 10 μm as determined by dynamic light scattering ISO 13320-1.

[0337] Table 10 describes the formation of a silicone acrylic emulsion where an acid-rich acrylic resin is blended with a silicone film-forming resin selected from Table 6, a neutralizer, and water and emulsified using Route 30, Blend C from Table 7.

[0338] Table 10: Silicone acrylic emulsion

[0339]

[0340] 1Dowsil 1-9770 is a mold release agent from Dow.

[0341] Table 11 describes the effect of the wt.% of silicone contained in the film-forming resin (silicone-modified polymer / silicone resin) and the wt.% of silicone on the ability of the acid-rich acrylic resin to form a stable emulsion over a long period of time, to be stable under dilution, and to clean up without solvents. This deficiency can be overcome by adjusting the monomers and / or monomer ratios used to produce the first stage acid-rich acrylic resin.

[0342] Table 11: Properties of silicone acrylic emulsions based on wt.% of silicone in silicone modified polymer / silicone resin

[0343]

[0344]

[0345] 1 = Worst, 5 = Best Water washability was assessed by dipping a spatula into the emulsion and washing the emulsion from the spatula blade in a steady stream using a wash bottle. This was done first from the bottom up, then on the reverse side from the top down to simulate dilution. If an "oil" layer or separation of the emulsion was observed, leaving polymer residue, the emulsion was considered unstable.

[0346] Table 12 describes the formation and properties of the silicone acrylic emulsion coating compositions.

[0347] Table 12: Silicone acrylic emulsion coating composition

[0348]

[0349]

[0350] Table 13 describes the formulation and properties of the basecoat to provide adhesion to the substrate and the topcoat to provide release.

[0351] Table 13: Primer and topcoat formulations

[0352]

[0353] Table 14 describes the formulation and characteristics of the silicone acrylic emulsion coating compositions and their properties.

[0354] Table 14: Silicone acrylic emulsion basecoat and topcoat compositions

[0355]

[0356] Example 7 - Pre-neutralized solvent-based coating formulation

[0357] In the previous examples, the acid-rich acrylic resin has been blended with the film-forming resin, neutralized and dispersed in water, although the neutralization and dispersion steps are not necessary to see performance benefits.

[0358] This example describes the formation of a solvent blend in which an acid-rich acrylic polymer is blended with a film-forming resin selected from Table 6 and formulated into a coating along with a pigment slip and flow aid and a release aid.

[0359] Table 15 describes the formation of acrylic / silicone polymer coating compositions from acidic polymers and film-forming resins.

[0360] Table 15: Acrylic / Silicone Polymer Coating Compositions

[0361]

[0362] Table 16 describes the properties of acrylic / silicone polymer coatings where a "pass" for 0T bend is a beneficial result, but not required, in various test results.

[0363] Table 16: Properties of acrylic / silicone polymer coatings

[0364]

[0365] Wherein specific examples of the present invention have been described above for the purpose of illustration, it will be apparent to those skilled in the art that many detail changes may be made to the present invention without departing from the present invention as defined in the appended claims. Therefore, the present application is intended to cover any variation, use or adaptation of the present disclosure using its general principles. Further, the present application is intended to cover such departures from the present disclosure within known or customary practices in the field to which the present disclosure belongs, and fall within the limitations of the appended claims.

Claims

1. A coating composition comprising: an acrylic emulsion comprising particles formed from a first polymer and a second polymer; The first polymer is polymerized from ethylenically unsaturated monomers including acid-containing monomers; The second polymer is chemically different from the first polymer, the second polymer being polymerized from ethylenically unsaturated monomers including a linking monomer; The first polymer and the second polymer have at least one of a cross-linking covalent bond and a non-covalent interaction between the acid-containing monomer of the first polymer and the linking monomer of the second polymer; a filler material, the filler material being present in an amount of at least 2 wt. % based on the total weight of the coating composition; and water. 2 . The coating composition according to claim 1 , wherein the first polymer has a content of the acid-containing monomer of 10 wt. % to 90 wt. % based on the total weight of the first polymer.

3. The coating composition according to any one of claims 1 to 2, comprising a non-aqueous solvent in a total amount of 10 wt.% or less based on the total weight of the coating composition.

4. The coating composition according to any one of claims 1 to 3, wherein the linking monomer of the second polymer comprises an epoxy functional group.

5. The coating composition according to any one of claims 1 to 4, further comprising a melamine-based crosslinking agent.

6. The coating composition of any one of claims 1 to 5, wherein the first polymer and the second polymer are polymerized in the absence of a chain transfer agent.

7. The coating composition of any one of claims 1 to 6, wherein the coating composition comprises less than 1 ppm total per- and polyfluoroalkyl substances (PFAS) based on the total weight of the coating composition, as determined by liquid chromatography tandem mass spectrometry (LC-MS / MS).

8. A method of coating a substrate with a coating composition, the method comprising: Applying the coating composition according to any one of claims 1 to 8 to the surface of the substrate; as well as The coating composition is cured to form a coating.

9. An article coated according to the method of claim 8, said article being selected from the group consisting of cookware articles, bakeware articles and cooking utensils.

10. The article of claim 9, wherein the coating comprises at least one of the following features: The dry film thickness (DFT) is at least 10 microns; According to ASTM D523 (2018) at 60 o The gloss measured at the bottom is at least 150; The result is passed when tested for 0T bend according to ASTM D4145 (2018); A pencil hardness of at least 5H at 20°C to 25°C according to ASTM D 3363 (2022); and The pencil hardness at a temperature of 400°F (204°C) is at least 3H according to ASTM D 3363 (2022).

11. An acrylic emulsion composition comprising: Aqueous medium; Neutralizing agents; and Emulsion particles comprising: a film-forming resin comprising a siloxane polymer; an acrylic polymer polymerized from ethylenically unsaturated monomers including an acid-containing monomer; and The film-forming resin is emulsified by the acrylic polymer in the aqueous medium. 12 . The emulsion composition according to claim 11 , wherein the acrylic polymer has a content of the acid-containing monomer of 20 wt. % to 70 wt. % based on the total weight of the acrylic polymer.

13. The emulsion composition according to claim 11 or claim 12, wherein the acrylic polymer is present in an amount of 2 wt.% to 15 wt.% based on the total weight of the acrylic polymer and the film-forming resin.

14. The emulsion composition of any one of claims 11 to 13, wherein the acrylic polymer can comprise an average particle size (D50) of 0.01 microns to 10 microns, as determined by dynamic light scattering according to ISO 13320-1 on a volume basis.

15. The emulsion composition according to any one of claims 11 to 14, wherein the film-forming resin comprises a hydrophobic polymer bonded to the siloxane polymer.

16. The emulsion composition according to any one of claims 11 to 15, wherein the neutralizing agent comprises an amine compound.

17. The emulsion composition of any one of claims 11 to 16, wherein the emulsion comprises less than 1 ppm total per- and polyfluoroalkyl substances (PFAS) based on the total weight of the coating composition, as determined by liquid chromatography tandem mass spectrometry (LC-MS / MS).

18. A method of coating a substrate with a coating composition, the method comprising: applying a coating composition to the surface of the substrate, the coating composition comprising the emulsion composition according to any one of claims 12 to 19; as well as The coating composition is cured to form a coating.

19. An article coated according to the method of claim 18, said article being selected from the group consisting of cookware articles, bakeware articles and cooking utensils.

20. The article of claim 19, wherein the coating comprises at least one of the following features: The dry film thickness (DFT) is at least 7 microns; According to ASTM D523 (2018) at 60 o The gloss measured at the bottom is at least 50; A pass result when tested for 0T bend according to ASTM D4145 (2018); and The pencil hardness according to ASTM D 3363 (2022) at a temperature of 20° C. to 25° C. is at least 3H.

21. A coating composition comprising: Solvent medium; a film-forming resin comprising a siloxane polymer; and An acrylic polymer polymerized from ethylenically unsaturated monomers including an acid-containing monomer, wherein the ethylenically unsaturated monomers have a content of the acid-containing monomer of 20 wt. % to 70 wt. % based on the total weight of the ethylenically unsaturated monomers.

22. The coating composition of claim 21, further comprising a filler material, the filler material being present in an amount of at least 2 wt. %, based on the total weight of the coating composition.

23. A coating composition according to claim 21 or claim 22, wherein the acrylic polymer is present in an amount of 2 wt.% to 15 wt.%, based on the total weight of the acrylic polymer and the film-forming resin.

24. The coating composition of any one of claims 21 to 23, wherein the emulsion comprises less than 1 ppm total per- and polyfluoroalkyl substances (PFAS) as determined by liquid chromatography tandem mass spectrometry (LC-MS / MS).

25. A method of coating a substrate with a coating composition, the method comprising: applying the coating composition according to any one of claims 21 to 24 to the surface of the substrate; as well as The coating composition is cured to form a coating.

26. An article coated according to the method of claim 25, said article being selected from the group consisting of cookware articles, bakeware articles and cooking utensils.

27. The article of claim 26, wherein the coating comprises at least one of the following features: The dry film thickness (DFT) is at least 10 microns; A pass result when tested for 0T bend according to ASTM D4145 (2018); and The pencil hardness according to ASTM D 3363 (2022) at a temperature of 20° C. to 25° C. is at least 4H.